Physicochemical Properties And Protein Digestibility Of Tuna By-Products Obtained Through Enzymatic Hydrolysis - Herpandi, Herpandi (2014)
Fish protein hydrolysate (FPH) is one of the emerging alternatives of the utilization of fish by-product, with a potential application in food industry. However, the application is still limited due to the occurrence of intense bitterness. Four commercially available enzymes including Neutrase® 1.5MG, Flavourzymes® 500 MG, Protamex® and Alcalase® 2.4L FG were chosen determine their ability to hydrolysis skipjack tuna dark flesh. Alcalase® 2.4L FG and Protamex® were found to give higher degree of hydrolysis and low content of free tryptophan in the FPH, compared to Neutrase® 1.5MG and Flavourzymes® 500 MG.